Energy drinks - product ingredients and their potential toxicity - Michał Jakub Sekuła; Natalia Kaleta; Piotr Pawłucki; Anna Maciak; Łukasz Domagalski; Ewelina Andrasz; Paulina Cuper (Kazimierz Wielki University, 2023)
Energy drinks (NE) are popular stimulants among adolescents and adults. They are commercial, advertised, widely available products that contain increased amounts of caffeine, and are designed to reduce feelings of fatigue in favor of increased mental and physical performance. In addition to caffeine, various ingredients such as vitamins, dyes or substances that impart a certain flavor are added to NEs. Many cases have been described of the harmful effects of NE used alone and in combination with alcohol on the human body: including on the digestive system, central nervous system, cardiovascular system or kidneys. We decided to analyze and compare with each other the composition of NEs from the most popular manufacturers available in most Polish grocery stores. We then briefly described the most important substances available in NE and reviewed the literature on their potential toxicity.  It is reasonable for physicians and teachers to educate young people and their parents about the harmfulness of NE, especially when children are suspected of taking large amounts. Further observations and studies monitoring the harmfulness of NEs are needed, and the drinks themselves should be subject to special surveillance.